Wasiat Wajibah bagi Anak Adopsi untuk Mendapat Harta Waris - Mila Yuniarsih; Hasyim Muzakki A. W.; Ika Viona Nur ’Aini; Zainatul Ilmiyah (Ma’mal: Jurnal Laboratorium Syariah dan Hukum, 2022)
Abstract: In Islamic Law, Adopted children are different from biological children in the division of inheritance. The biological child is entitled to an inheritance, while the adopted child is not an heir, so he not is entitled to an inheritance. However, he is entitled to a maximum of 1/3 of the inheritance through a mandatory will. This becomes a question, what happens when parents want to give inheritance to their adopted children. This research discusses the mandatory will for adopted children to get inheritance by analyzing the Palembang Religious Court Decision No. 35/Pdt.G/2018/PTA. This research is a type of literature research. The nature of his research is descriptively analytical, using a qualitative approach. The primary data source used is the Palembang Religious Court Decision No. 35/Pdt.G/2018/PTA. Plg while secondary data in the form of books and journal articles. The collected data is then organized, edited and analyzed through deductive analogies. The results of the study yielded two conclusions. First, in Court Decision No. 35/Pdt.G/2018/PTA. PLg, the judge granted inheritance rights to adopted children through compulsory wills under article 209 of the Compilation of Islamic Law and the benefit of adopted children. Because both parents have died, the adopted child gets 1/6 of each adoptive parent so that it does not exceed 1/3 of the inheritance.  Second, from the Islamic law perspective, Court Decision No. 35/Pdt.G/2018/PTA. PLg on the will of the obligatory has been in accordance with Islamic law. Keywords: Adoption, compulsory wills, inheritance, Islamic law.   Abstrak: Dalam Hukum Islam, status anak angkat berbeda dengan anak kandung dalam pembagian warisan. Anak kandung berhak mendapat warisan, sedangkan anak angkat ia bukan ahli waris sehinggat tidak berhak mendapat warisan. Hal ini menjadi pertanyaan, bagaimana ketika orang tua ingin memberikan peninggalan kepada anak angkat. Penelitian ini membahas tentang wasiat wajibah bagi anak angkat untuk mendapat harta waris dengan menganalisis Putusan Pengadilan Agama Palembang Nomor 35/Pdt.G/2018/PTA. Penelitian ini berjenis penelitian pustaka. Sifat penelitiannya adalah deskriptif analitis dengan menggunakan pendekatan kualitatif. Sumber data primer yang digunakan yakni Putusan Pengadilan Agama Palembang Nomor 35/Pdt.G/2018/PTA. Plg  sedangkan data sekunder berupa buku dan artikel jurnal. Data yang terkumpul kemudian diatur, disunting dan dianalisis melalui analogi deduktif. Hasil penelitian menghasilkan dua kesimpulan. Pertama, dalam Putusan Pengadilan Agama Palembang No. 35/Pdt.G/2018/PTA.PLg, hakim memberikan hak waris pada anak adopsi melalui wasiat wajibah berdasarkan pasal 209 Kompilasi Hukum Islam dan kemaslahatan anak adopsi. Karena kedua orang tuanya telah meninggal dunia, maka anak angkat mendapat 1/6 dari masing-masing orang tua angkat sehingga tidak melebihi 1/3 harta waris. Kedua, ditinjau dari hukum Islam Putusan Pengadilan No. 35/Pdt.G/2018/PTA.PLg tentang wasiat wajibah telah sesuai dengan Hukum Islam. Kata kunci: Adopsi, wasiat wajibah, waris, hukum Islam.